The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1212/wnl.53.9.1910
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surgery for Parkinson’s disease

Abstract: the Task Force on Surgery for Parkinson's Disease* PD is a common disorder affecting on average 100 per 100,000 population. Despite the large number of medications available for the treatment of early and moderately advanced PD, options specifically designed for the patient with advanced disease are limited. Surgery for PD dates from 1939-1940, when Bucy and Case 1 and Klemme 2 excised parts of the cerebral cortex to treat tremor and dystonia, but this type of surgery produced hemiparesis. Surgical basal gangl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 101 publications
1
37
0
Order By: Relevance
“…Older studies, including adrenal medulla implants and foetal implant studies, were reviewed by Rehncrona [13]. On behalf of the American Academy of Neurology, Hallett and Litvan reported the evaluation of clinical studies in patients with PD in which a range of experimental functional surgical procedures were employed [14]. Their summary of the evaluation of implantation of human foetal ventral mesencephalon tissue and cells concluded that foetal tissue transplants were well-tolerated and that morbidity and mortality were low.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Older studies, including adrenal medulla implants and foetal implant studies, were reviewed by Rehncrona [13]. On behalf of the American Academy of Neurology, Hallett and Litvan reported the evaluation of clinical studies in patients with PD in which a range of experimental functional surgical procedures were employed [14]. Their summary of the evaluation of implantation of human foetal ventral mesencephalon tissue and cells concluded that foetal tissue transplants were well-tolerated and that morbidity and mortality were low.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…These motor symptoms are commonly treated with levodopa and dopamine agonists [2], but in medically intractable cases and/or those associated with L-dopa induced dyskinesias, surgical techniques are performed [3]. In addition to motor symptoms, specific cognitive dysfunctions are observed in PD patients, concerning visual perception and visuo-spatial abilities [4][5][6][7][8] habit memory, affected more than declarative memory [9], short-term memory, disturbed to larger extent than long-term memory [10], working memory and executive functions [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Among stereotactic ablative surgeries, to alleviate bradykinesia, rigidity and dyskinesias, pallidotomy is recommended [3]. In a previous study, we explored the cognitive outcome of both unilateral stereotactic thalamotomy and pallidotomy [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stereotactic thalamotomy is a mainstay in the surgical treatment of Parkinson's disease (PD)-related tremor or essential tremor [1][2][3][4][5]. However, to treat lower-extremity tremor, the thalamic ablation surgery is not favored, and is even a matter of potential concern, since selective lesions must be placed dorsolaterally in the thalamic ventral intermediate nucleus (Vim) where they are adjacent to the internal capsule [2,6].…”
Section: Introductionmentioning
confidence: 99%